PENGENDALI LAMPU MONITORING RUMAH DENGAN SHORT MESSAGE SERVICE (SMS) BERBASIS ARDUINO UNO - Mohammad Taufan Asri Zaen; Asep Yunandy (LPPM STMIK Lombok, 2018)
The increasing activity of someone outside the home causes difficulties in controlling the lamps and monitoring the condition of the house from a distance, therefore it is necessary to control the lamps remotely. This research designed and built a lamps handling by short message service (SMS) based on arduino uno. Lamps handling by sms is a tool which act as the lamp and alarm switches at house, whenever without time limits as far as the GSM signal is still can be reached. Handling tool from distance by mobile sms act as an order producer, arduino uno as a microcontroller, sensor peer as a movement detector, gsm modul sim 900A as an information sender and acceptor and relay as a switcher of lamps or the alarms. The test results of this tool show that this too can be used based on the order which is given from distance to control the lamps and the alarms. Another function of this tool is to monitor the lamps condition by â€œcekâ€ function to know in which lamp is on or off mode. It also can switch on an alarm and send some sms to the ownerâ€™s contact number when its sensor detected any object movements.